O olhar das crianças sobre sua participação no cotidiano da educação infantil - Menezes, Amanda Fhilladélfia Bezerra Silva de (2024)
This study, entitled "The children's view of their participation in the daily routine of Early Childhood Education", arose from the need to study the subject based on the challenges experienced by the researcher in relation to the active participation of children in the daily routine of early childhood education, as an Early Childhood Education teacher, and the scarcity of research dealing with the subject, mainly based on the perspective of the children themselves. This is research with children, as Oliveira-Formosinho and Araújo (2007) and Cruz (2008) advocate. In this research perspective, children are not considered to be the object of the research, but are seen as participating subjects. The study is based on the Pedagogy of Childhood, which recognizes the child as a subject with rights, active, who reads and interprets the world, who constructs knowledge and culture, someone who is capable and competent, as well as defending the child's participation in pedagogical practices Oliveira-Formosinho (2007). The locus of the study was a Municipal Early Childhood Education Center - CMEI, in the city of Natal/RN, in a level IV class, with children aged between 5 and 6. The research question was as follows: "How do the children in a level IV class at a CMEI in the city of Natal/RN perceive their participation in Early Childhood Education?" and the object of study was "Children's participation in the daily routine of Early Childhood Education". In order to answer the research question, the general objective was: to understand how the children in the level IV Early Childhood Education class perceive their participation in everyday school life. And specific: to identify what the children understand as participation; to specify, from the children's perspective, the moments of participation in the daily routine of Early Childhood Education; to understand at which moments in the daily routine of Early Childhood Education the space for children to speak and listen is provided. The research is inspired by the ethnographic approach, based on André (1995), Rocha (2008), Sarmento (2010) and Friedman (2011). The methodological tools adopted were participant observation (Friedman, 2016), guided by an observation tool and individual and collective interviews with 8 (eight) children in the class. To support the discussion about children's participation, we relied on the studies of Hart (1992), Oliveira-Formosinho (2007 and 2008), Formosinho and Oliveira-Formosinho (2013) and Fernandes (2009 and 2016), who discuss children's active participation and their central place in the pedagogical practices of Early Childhood Education. As a result of the research, it emerged that the children define participation as an action and point to every moment of the routine as participation, which is different from what scholars in the field point out when they emphasize that participation happens when there is listening and negotiation between adults and children, when the children understand the objectives of the proposed activities and when these actions have meaning for the subjects who carry them out. Therefore, based on the research carried out, it was possible to conclude that children's effective participation in the day-to-day life of Early Childhood Education is still little experienced.